2021
DOI: 10.3390/mi12080850
|View full text |Cite
|
Sign up to set email alerts
|

Micromask Lithography for Cheap and Fast 2D Materials Microstructures Fabrication

Abstract: The fast and precise fabrication of micro-devices based on single flakes of novel 2D materials and stacked heterostructures is vital for exploration of novel functionalities. In this paper, we demonstrate a fast high-resolution contact mask lithography through a simple upgrade of metallographic optical microscope. Suggested kit for the micromask lithography is compact and easily compatible with a glove box, thus being suitable for a wide range of air-unstable materials. The shadow masks could be either ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…24 The thickness of the flakes was determined using the atomic force microscopy. van der Waals heterostructures out of these flakes were then assembled on the Al 2 O 3 substrate with a preliminary lithographically defined 25 array of binary markers. We used a dry hot pick up technique 26 with a homemade transfer machine 27 at ambient conditions.…”
mentioning
confidence: 99%
“…24 The thickness of the flakes was determined using the atomic force microscopy. van der Waals heterostructures out of these flakes were then assembled on the Al 2 O 3 substrate with a preliminary lithographically defined 25 array of binary markers. We used a dry hot pick up technique 26 with a homemade transfer machine 27 at ambient conditions.…”
mentioning
confidence: 99%
“…94 Poor quality photomasks, focus, or alignment can result in distorted patterns or defects. 95 Photolithography has also been widely implemented in the creation of 2D devices. 96 Using simple top-down approaches, Zhao et al 96 demonstrated wafer-scale nanoribbon field-effect transistor (FET) biosensors (Fig.…”
Section: Fabrication Processes Of 2d Materials-based Wearable Chemica...mentioning
confidence: 99%
“…It can be mitigated by using a thinner photoresist to improve image contrast [ 56 ]. Recently, Pugachev et al demonstrated the feasibility of manufacturing low-cost micro masks using contact lithographic methods, allowing for the straightforward scaling up of 2D materials microstructure fabrication [ 57 ]. The constructed micro mask can achieve resolutions on the order of micrometers (~0.6 μm).…”
Section: Fabrication Techniquesmentioning
confidence: 99%